Implications of refrigerator management on subjective memory complaints among Japanese community‐dwelling older adults. Issue 1 (9th October 2022) - Ikeda, Yuriko; Maruta, Michio; Han, Gwanghee; Miyata, Hironori; Nakamura, Atsushi; Shimokihara, Suguru; Tabira, Takayuki
Abstract: Aim: Older adults with subjective memory complaints (SMC) may experience very minor difficulties in daily activities. Although caregivers and occupational therapists who support community‐dwelling older adults are aware of the existence of characteristic behaviours related to refrigerator management, no specific studies have been conducted. This study aimed to examine the implications of refrigerator management for older adults with SMC. Methods: A self‐administered questionnaire was sent to 3000 randomly selected members of Consumer's Co‐operative Kagoshima. Of the returned responses, a total of 282 older adults were analyzed. Analyzed subjects were divided into two groups: SMC (+) group ( n  = 74) and SMC (−) group ( n  = 192). A questionnaire was created by four occupational therapists and used to assess the characteristics of analyzed subjects and their abilities to manage the refrigerator. The observation list for early signs of dementia was also utilised. A multiple logistic analysis was performed to examine the association between SMC and refrigerator management. Results: The SMC (+) group had a significantly higher number of refrigerator management errors than the SMC (−) group ( P  = 0.008). The SMC (+) group had more errors than the SMC (−) group in the following four items regarding refrigerator management; the refrigerator has a lot of the same foods / expired food, the person does not know what's in the refrigerator, the person cannot find what he/she needs in the refrigerator. Moreover, SMC was associated with the item 'the person does not know what is in the refrigerator' (odds ratio 7.44, 95% CI 1.51–43.8, P  = 0.02). Conclusions: Our results showed that older adults with SMC had several problems regarding refrigerator management. Evaluating refrigerator management among older adults with SMC may help consider multifaceted support.